2017
DOI: 10.1109/tbme.2016.2605578
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Electrophysiological Study of Induced Ventricular Tachycardia in Intact Rat Model of Chronic Ischemic Heart Failure

Abstract: The in vivo rat model of CHF combined with EP analysis could be used to determine the arrhythmogenic potential of new treatments for CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…However, after 2 weeks, the APD begins to increase and returns to normal values after 8 weeks. Similarly, normal APD values were also found in murine epicardial BZ tissue 6 weeks after MI (Weigand et al, 2016 ), suggesting that the healing process is complete earlier in this species.…”
Section: Review Of Experimental Data Of the Electrophysiological Rmentioning
confidence: 63%
See 2 more Smart Citations
“…However, after 2 weeks, the APD begins to increase and returns to normal values after 8 weeks. Similarly, normal APD values were also found in murine epicardial BZ tissue 6 weeks after MI (Weigand et al, 2016 ), suggesting that the healing process is complete earlier in this species.…”
Section: Review Of Experimental Data Of the Electrophysiological Rmentioning
confidence: 63%
“…APD shortening was also found in feline (Wong et al, 1982 ; Kimura et al, 1986 ), although measurements of neither I CaL nor I KAS were reported in those studies. On the other hand, the canine (Gardner et al, 1985 ; Ursell et al, 1985 ), porcine (Denisko et al, 2017 ), murine (Weigand et al, 2016 ), and human (Dangman et al, 1982 ) BZ of healed infarcts exhibit normal APD, while APD prolongation has also been found in rabbits with healed infarcts (Litwin and Bridge, 1971 ).…”
Section: Review Of Experimental Data Of the Electrophysiological Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole-heart in vivo electrical pacing from healthy tissue near the apex of the LV was performed using a function generator. 16…”
Section: Echocardiographymentioning
confidence: 99%
“…Rats are the most commonly used laboratory animal for assessing ischemia-reperfusion injury in experiments. They are used to study the mechanisms of post-infarction pathology and to develop approaches reducing adverse cardiac events following ischemia-reperfusion injury in the myocardium [5][6][7]. In addition to experimental studies, an anatomically accurate computer modeling of the heart has become a valuable process for investigations of cardiac arrhythmia mechanisms.…”
Section: Introductionmentioning
confidence: 99%